Biofilm development in microbial support made from solid wastes for bioreactor for treatment of wastewater during start-up - Fidero, Kuok (2008)
The development of biofilm in microbial support made of plastic wastes and pyrolyzed biomass was studeid. An anaerobic baffled filter reactor with internal dimensions of 120 cm L x 60 cm W x 60 H was operated and the biofilm growth was observed during start-up. The microbial support studied was coconut shell charcoal ( 1 cm diameter random shape) packed in perforated 80 ml plastic bottles yakult, which was in turn packed in perforated 6-L plastic mineral water. The other system was charcoal packed in cylindrical plastic screens. For more uniform observation, doughnut shaped charcoal (1 cm OD) was used for sampling purpose. During the first stage of operation with 8 hours feeding, 8 hours recycling, and 8 hours settling the highest COD removal efficiency was 87% at an OLR of 0.2 kg COD/m3. day. higher removal efficiency was achieved during the second stage of operation when the pH in the reactor was maintained above 6.2 by recycling some of the effluent and without addition of NaHCO3. The highest COD removal was 95% at an OLR of 0.8 kg COD/m3. The greates growth of biomass in yakult and plastic screen bottle were observed in chamber 4 at the 30th day with a value of 15.9 and 40.8 mg/g support material, respectively. The results show that the anaerobic baffled filter reactor with solid wastes as microbial support provides good COD removal. The large surface area of regularly-shaped coconut shell charcoal allowed fast colonization of active biomass. The observation of biomass growth using SEM and light microscope confirmed that colonization of biofilms existed after day 20 with the presence of two morphologies, cocci and bacilli.